International trends in the incidence of malignant melanoma 1953–2008—are recent generations at higher or lower risk? - Erdmann, Friederike; Lortet‐Tieulent, Joannie; Schüz, Joachim; Zeeb, Hajo; Greinert, Rüdiger; Breitbart, Eckhard W.; Bray, Freddie (International journal of cancer, 2013)
The incidence of cutaneous malignant melanoma has steadily increased over the past 50 years in predominately fair‐skinned populations. This increase is reported to have leveled off recently in several Northern and Western European countries, Australia, New Zealand and in North America. We studied the global patterns and time trends in incidence of melanoma by country and sex, with a focus on and age‐ and cohort‐specific variations. We analyzed the incidence data from 39 population‐based cancer registries, examining all‐ages and age‐truncated standardized incidence rates of melanoma, estimating the annual percentage change and incidence rate ratios from age‐period‐cohort models. Incidence rates of melanoma continue to rise in most European countries (primarily Southern and Eastern Europe), whereas in Australia, New Zealand, the U.S., Canada, Israel and Norway, rates have become rather stable in recent years. Indications of a stabilization or decreasing trend were observed mainly in the youngest age group (25–44 years). Rates have been rising steadily in generations born up to the end of the 1940s, followed by a stabilization or decline in rates for more recently born cohorts in Australia, New Zealand, the U.S., Canada and Norway. In addition to the birth cohort effect, there was a suggestion of a period‐related influence on melanoma trends in certain populations. Although our findings provide support that primary and secondary prevention can halt and reverse the observed increasing burden of melanoma, they also indicate that those prevention measures require further endorsement in many countries.